2022
DOI: 10.1111/jfbc.14109
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of propolis on myocardial ischemia/reperfusion injury in males and ovariectomized females but not in intact females

Abstract: The aim of this study is to investigate the effect of propolis, which may have estrogenic effects, on myocardial ischemia/reperfusion (mI/R) injury not only in male rats but also in intact and ovariectomized (ovx) female rats. Six groups were formed: untreated males (n = 8), treated males (n = 9), untreated intact females (n = 9), treated intact females (n = 10), untreated ovx females (n = 10), and treated ovx females (n = 8).An alcoholic extract of a single dose of propolis (200 mg/kg) was administered orally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…MicroRNA (miRNA) is a kind of short chain, nonencoding, single-strand small molecule RNA with posttranscriptional regulation function discovered in recent years [ 11 ]. The research shows that miRNA is involved in the maturation and follicular development of mouse oocytes [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNA (miRNA) is a kind of short chain, nonencoding, single-strand small molecule RNA with posttranscriptional regulation function discovered in recent years [ 11 ]. The research shows that miRNA is involved in the maturation and follicular development of mouse oocytes [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, IR + hearts from OVX rats showed higher recovery of CFI and lower infarct size following nitrate administration. Reduced CFI and increased infarct size in rats following 2 (Kaya and Agan, 2022), 4 (Ibañez et al, 2022), 5 (Ibañez et al, 2022), 6 (Garvin et al, 2017, 12 (Kumar et al, 2021), and 44 weeks of ovariectomy have previously been documented. Our findings align with previous studies (summarized in Table 4) showing reduced infarct size and improved post-ischemic cardiac function in healthy mice following short-term nitrate administration (7 days) at doses of Levels of infarct size in the ischemia-exposed hearts from OVX and OVX + N rats.…”
Section: Discussionmentioning
confidence: 87%
“…Reduced tolerance against myocardial ischemia-reperfusion (IR) injury and increased infarct size by 45%–75% has been reported in ovariectomized (OVX) rats following 2 ( Kaya and Agan, 2022 ), 6 ( Garvin et al, 2017 ), 12 ( Kumar et al, 2021 ), and 44 ( Yousefzadeh and Jeddi, 2023 ) weeks after ovariectomy. We previously reported that these effects of OVX in heart tissue are at least in part associated with reduced nitric oxide (NO) levels, reduced endothelial NO synthase (eNOS) expression, and increased inducible NOS (iNOS) expression ( Yousefzadeh and Jeddi, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Raw PP was harvested during the summer season. In previous studies, ethanol extraction of PP was used because the strongest antioxidant activity of PP was in the extractions obtained with ethanol solvent (16,17). Therefore, we have used ethanol as a solvent of the PP.…”
Section: Preparation Of Propolis Extractionmentioning
confidence: 99%
“…Therefore, we have used ethanol as a solvent of the PP. The content of PP used had been determined in previous study (16).…”
Section: Preparation Of Propolis Extractionmentioning
confidence: 99%